Effect of pre-oxidation on low pressure membrane (LPM) for water and wastewater treatment: A review. (September 2019) - Li, Kai; Wen, Gang; Li, Shu; Chang, Haiqing; Shao, Senlin; Huang, Tinglin; Li, Guibai; Liang, Heng
Abstract: Low pressure membrane (LPM) filtration is a promising technology for drinking water production, wastewater reclamation as well as pretreatment for seawater desalination. However, wider implementation of LPM is restricted by their inherent drawbacks, i.e., membrane fouling and insufficient rejection for dissolved contaminants. Pretreatment of feed water is a major method to improve the performance of LPM, and pre-oxidation has gained extensive attention because it can significantly alter compositions and properties of feed water through chemical reactions. This paper attempts to systematically review efficiency and mechanisms of pre-oxidation in membrane fouling control and permeate water quality improvement. On the basis of briefly discussing major foulants and fouling mechanisms of LPM, advantages and disadvantages of pre-oxidation in mitigating organic fouling, inorganic fouling and biofouling are discussed in detail. Impacts of pre-oxidation on removal of micropollutants, bulk organic matter and inorganic pollutants are summarized, and potential by-products of different oxidants are presented. As a prerequisite for the integration of chemical oxidation with LPM filtration, compatibility of membrane with oxidants at low concentration and long exposure time are highlighted. Finally, the existing challenges and future research needs in practical application of chemical oxidation to improve performance of LPM are also discussed. Graphical abstract: Image 1 Highlights: Effect of pre-oxidation on fouling and permeate quality of LPM is reviewed. Pre-oxidation effectively mitigates fouling caused by high-MW organics and bacteria. Pre-oxidation enhances removal of micropollutants and inorganic pollutants. Compatibility of polymeric membrane with oxidants requires further investigation.